Protective Effect of Lactobacillus plantarum P8 on Growth Performance, Intestinal Health, and Microbiota in Eimeria-Infected Broilers - Wang, Yang; Lv, Xiaoguo; Li, Xuemin; Zhao, Jinshan; Zhang, Kai; Hao, Xiaojing; Liu, Kaidong; Liu, Huawei (Frontiers in Microbiology, 2021)
Coccidiosis is one of the major parasitic diseases in the commercial broiler industry. Probiotics can protect poultry against Eimeria infection. However, the mechanisms are not fully known. Therefore, Lactobacillus plantarum P8 (P8) was used to investigate its anti-coccidial property and mechanism. Five hundred broilers were allocated to five treatments: control diet (NC), control diet + Eimeria infection (IC), control diet containing 1 × 107 cfu/g P8 + Eimeria infection (P8L), control diet containing 1 × 108 cfu/g P8 + Eimeria infection (P8H), and control diet + Eimeria infection + Diclazuril (DIC). At day 14, all treatments except NC were inoculated with sporulated oocysts. Results indicated that Eimeria infection increased the mortality and oocysts shedding, and declined the growth performance as well as the intestinal barrier in Eimeria-treated broilers. On the contrary, dietary supplementation of low level P8, high level P8 and DIC decreased the mortality and oocysts shedding, but improved the growth performance and intestinal barrier. The impaired intestinal morphology in the IC group was also improved by P8H and DIC treatments. Besides, the elevated oxidative stress and pro-inflammation in Eimeria-infected broilers were reduced by P8L, P8H and DIC treatments. Metagenomic analysis indicated P8 altered the structure of the gut microbiota, and the alteration was more obvious at day 21 than day 42. Notably, IC also increased the abundances of Eimeriidae, Eimeria and Eimeria tenella at day 21, while P8L and DIC decreased the abundances. Correlation analysis revealed that bacteria in Eimeria-treated broilers positively correlated with the intestinal permeability, oxidative stress and inflammation, while bacteria in broilers receiving P8L and DIC negatively correlated with the aforementioned pathological indices. Functional prediction demonstrated that the metagenomes of Eimeria-infected broilers were involved in several diseases. But the metagenomes of P8L-treated broilers were involved in energy metabolism and replication repair. In conclusion, dietary P8 supplementation inhibited oocyst shedding and improved the growth performance as well as the intestinal health of broilers infected with Eimeria, which was closely related to the regulation of gut microbiota. Moreover, the effects of P8 may be more effective in the early infection of coccidia.